The additional records for the flora of Istanbul [A2(A) Istanbul: Omerli, Formula 1 Area - (:unkn) unknown (My University, 2007)
In this paper, 9 taxa are added to the flora of Istanbul with the specimens collected grown Omerli district, Asiatic part of Istanbul, additionally the presence of Stellaria nemorum L. subsp.nemorum in Turkey is confirmed.
Keywords: Istanbul; New records; Stellaria nemorum L. subsp. nemorum; Turkish Flora